Factors to Assist Micro and Small Manufacturing Enterprises with New Product Commercialization in Brits and Surrounding Areas. - Malan, Regan (Journal of Applied Research and Multidisciplinary Studies, 2022)
Abstract Purpose - The purpose of the paper is primarily to identify the prevalence of factors needed by micro and small enterprises which influence successful commercialization of new products in Brits and surrounding areas. Design Methodology - A non-experimental form of research was utilized, where a descriptive research design was employed. A survey questionnaire was compiled and quantitative research approach was used. Findings - There were 103 responses out of a targeted sample of 200 respondents. This constitutes a response rate of 51.2%. The majority of the responses were from the micro enterprises. The majority of enterprises were in Brits and surrounding areas with a total of 54% micro enterprises (n = 56). Research limitations and implications - The research project was limited to micro and small manufacturing companies in one area of South Africa. Practical implications - Small businesses are important partners in economic development, job creation and equity and that their success is paramount. This is embedded in the government’s National Development Plan 2030. Originality / Value - The success of new product commercialization in micro and small manufacturing enterprises is of utmost importance to ensure the success and sustainability of companies.